Performance of van der Waals DFT approaches for helium diffraction on metal surfaces. (4th February 2019) - del Cueto, Marcos; Maurer, Reinhard J; Al Taleb, Amjad; Farías, Daniel; Martín, Fernando; Díaz, Cristina
Abstract: The ability of the different approaches proposed to date to include the effects of van der Waals (vdW) dispersion forces in density functional theory (DFT) is currently under debate. Here, we used the diffraction of He on a Ru(0 0 0 1) surface as a challenging benchmark system to analyze the suitability of several representative approaches, from the ones correcting the exchange-correlation generalized gradient approximation (GGA) functional, to the ones correcting the DFT energies through pairwise-based methods. To perform our analysis, we have built seven continuous potential energy surfaces (PESs) and carried out quantum dynamics simulations using a multi-configuration time-dependent Hartree method. Our analysis reveals that standard DFT within the PBE-GGA framework, although it overestimates diffraction probabilities, yields the best results in comparison with available experimental measurements. On the other hand, although several of the existing vdW DFT approaches yield physisorption wells in very good agreement with experiment, they all seem to overestimate the long-distance corrugation of the PES, the region probed by He scattering, resulting in a large overestimation of diffraction probabilities.